1. ## difficult question!!!!

$\log_{\tan(\frac{\pi}{4}+\frac{x}{2})} (\sec x + \tan x)-\log_{\tan(\frac{\pi}{4}-\frac{x}{2})} (\sec x - \tan x)$

Hello jashansinghal
Originally Posted by jashansinghal
$\log_{\tan(\frac{\pi}{4}+\frac{x}{2})} (\sec x + \tan x)-\log_{\tan(\frac{\pi}{4}-\frac{x}{2})} (\sec x - \tan x)$
So what is the question?

3. $\sec x+\tan x=\frac{1}{\cos x}+\frac{\sin x}{\cos x}=\frac{1+\sin x}{\cos x}=\frac{\sin^2\frac{x}{2}+\cos^2\frac{x}{2}+2\sin \frac{x}{2}\cos\frac{x}{2}}{\cos x}=$

$=\frac{\left(\cos\frac{x}{2}+\sin\frac{x}{2}\right )^2}{\left(\cos\frac{x}{2}-\sin\frac{x}{2}\right)\left(\cos\frac{x}{2}+\sin\f rac{x}{2}\right)}=$

$=\frac{\cos\frac{x}{2}+\sin\frac{x}{2}}{\cos\frac{ x}{2}-\sin\frac{x}{2}}=\frac{1+\tan\frac{x}{2}}{1-\tan\frac{x}{2}}=\tan\left(\frac{\pi}{4}+\frac{x}{ 2}\right)$

Then $\log_{\tan\left(\frac{\pi}{4}+\frac{x}{2}\right)}( \sec x+\tan x)=1$

In the same way, $\log_{\tan\left(\frac{\pi}{4}-\frac{x}{2}\right)}(\sec x-\tan x)=1$

Then the expression is 0.